Till death (or divorce) do us part: Early-life family disruption and investment behavior - André Betzer; Peter Limbach; P. Raghavendra Rau; Henrik Schürmann (University of Cologne, Centre for Financial Research (CFR), 2021)
We document a long-lasting association between a common societal phenomenon, early-life family disruption, and investment behavior. Controlling for socioeconomic status and family background, we find fund managers who experienced the death or divorce of their parents during childhood exhibit a stronger disposition effect, take lower risk, and are more likely to sell their holdings following risk-increasing firm events. The results are consistent with persistent symptoms of post-traumatic stress and strengthen as treatment intensifies. The evidence adds to our understanding of the role of social factors and "nurture" in finance as well as the origin of investment biases.
Keywords: G11; G23; G41; 330; Disposition effect; Family disruption; Feelings; Formative experience; Investor behavior; Risk-taking; Social finance